Brave as a mountain lion - Scott, Ann Herbert; Coalson, Glo (New York : Clarion Books, 1996)
Spider is afraid to get up on stage in front of everybody in the school spelling bee, but after listening to his father's advice, decides that he too will try to be as brave as his Shoshoni ancestors.
Keywords: Courage; Stage fright; Schools; Shoshoni Indians; Indians of North America